Sensibilidade a dicas sociais humanas e comportamentos emergentes em cães domésticos (Canis familiaris) - Zaine, Isabela (2015)
Animal experimentation with several species contributes to knowledge and understanding of different learning principles and aspects of human behavior. The domestic dog has been appointed as interesting to the comparative study with humans because of the long history of sharing the same physical and social environment. Among the lines of research pursued with dogs, two are of greater importance for the studies presented in this Thesis: sensitivity to human social cues and investigation of potentially symbolic behavior. Article 1 aimed to investigate the role of ontogenetic learning in the sensitivity to social cues of puppies in two experiments. The main results showed that exposure to human social environment had a significant impact on the performance of subjects, as well as the different degrees of salience of the social cues. Article 2 provides a number of experimental techniques used in studies with dogs, monkeys and bees in attempts to establish visual arbitrary conditional relations between stimuli. These techniques were insufficient to produce such a repertoire in dogs and bees and were partially effective with capuchin monkeys. For dogs, there was a prominent interference of preference for positions or stimuli during the procedure. Article 3 presents an experiment of responding by exclusion in a context of simple discrimination with adult dogs. The results showed evidence of exclusion responding for almost all subjects. Finally, Article 4 aimed to replicate the exclusion results presented in Article 3, adding some experimental controls, and evaluate emergent learning as a result of exclusion trials. The data pointed that, again, the dogs showed exclusion responding, however, learning of new functions of stimuli only occurred after a few repetitions of exclusion trials. Combined, these results add data to the literature of behavioral repertoire with dogs and basic learning processes regarding both sensitivity to social cues and symbolic behavior.